Elevated alanine aminotransferase levels in HIV-infected persons without hepatitis B or C virus coinfection - Alghamdi, Saad (Ann Saudi Med, 2016)
BACKGROUND: Mortality related to human immunodeficiency (HIV) has improved with the use of antiretroviral therapy; however, liver disease–related mortality remains a major concern for the HIV population. Elevation of alanine aminotransferase (ALT) has been noted in HIV-infected persons even without viral hepatitis infection. OBJECTIVE: The objective of this study was to determine the incidence and prevalence of chronic alanine ALT elevation among patients infected with HIV who are negative for hepatitis B or C infection. DESIGN: Retrospective chart review. SETTINGS: We reviewed the medical records of all patients infected with HIV who had been treated from November 2002 to December 2010. PATIENTS AND METHODS: Patients with an unknown or positive HBV or HCV infection status were excluded. We identified patient demographics, route of transmission, peak viral load, and nadir CD4 count. RESULTS: We followed 440 patients for up to 2265 person-years. A total of 123 patients developed chronically elevated ALT levels, with an incidence of 5.8 cases per 100 person-years. Chronically elevated ALT levels were associated with high HIV viral load, mean body mass index, and diabetes mellitus. We found exposure to lamivudine in 58% of the patients, efavirenz in 41%, and zidovudine in 38%. Abdominal ultrasounds revealed fatty liver in 20 of 39 (51%) of the patients. CONCLUSION: Among patients without viral hepatitis coinfection, the prevalence and incidence of chronic elevated ALT levels were high and accompanied by high HIV RNA levels and increased BMI. LIMITATIONS: The limitations of this report are its retrospective nature and lack of a control group.